Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.47750/pnr.2022.13.04.079
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Streptococcus Agalactiae Biofilm Formation in Response to Purified Phytochemical Antimicrobial Materials

Abstract: Group B streptococci (GBS) are globally recognized to cause adverse pregnancy outcomes, such as stillbirths and miscarriages, and are one of the main causes of newborn sepsis and meningitis. The high resistance of GBS to antibiotics becomes difficult or impossible to treat, becoming increasingly common, causing a global health crisis. It complicates their eradication, potentially leading to the development of chronic infections. A total of 181 specimens were obtained from pregnant women. Out of these specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…The active substance (SAL) can be released upon skin application, potentially modifying properties, such as texture, hydration, and elasticity, or promoting a healing effect. As shown in previous reports [32][33][34], regular external application of salicin and its derivatives effectively reduces wrinkles and sagging of the skin and muscles after wounds have been repaired. They also protect the skin from bacterial and fungal infections.…”
Section: Release Process Of Salicinmentioning
confidence: 56%
See 1 more Smart Citation
“…The active substance (SAL) can be released upon skin application, potentially modifying properties, such as texture, hydration, and elasticity, or promoting a healing effect. As shown in previous reports [32][33][34], regular external application of salicin and its derivatives effectively reduces wrinkles and sagging of the skin and muscles after wounds have been repaired. They also protect the skin from bacterial and fungal infections.…”
Section: Release Process Of Salicinmentioning
confidence: 56%
“…Moreover, various studies described in the literature have shown that, due to its antimicrobial and anti-biofilm properties, salicin can be used in dressing materials as a natural drug in wound-dressing systems with intrinsic antibacterial activity, in the form of hydrogels or films [32,33]. Salicin and its derivatives are excellent cures for skin diseases and infections.…”
Section: Introductionmentioning
confidence: 99%